2015
DOI: 10.2308/accr-51222
|View full text |Cite
|
Sign up to set email alerts
|

Banks' Acquisition of Private Information about Financial Misreporting

Abstract: This study investigates whether banks respond to financial misreporting as the borrowing firms release misstated financial reports, i.e., in the misreporting period. Drawing upon finance theory that recognizes banks' superior information access and processing abilities, this study predicts and finds that banks adjust loan contract terms in response to the ongoing misreporting. Compared with loans issued in the prior period, loans issued in the misreporting period have higher interest spread, are more likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…We see that loans to firms that will restate in the future have interest rate spreads that are 27.64 basis points higher, on average, than comparable loans, after controlling for other predictors of loan spread. This supports the notion that banks have superior information access and processing skills relative to equity market participants because they can anticipate future restatements at the loan initiation date (Chen 2016). Moreover, we find some evidence that lenders are better able to anticipate future restatements when the loan initiation is preceded by one or more peer irregularities.…”
Section: Notessupporting
confidence: 84%
See 1 more Smart Citation
“…We see that loans to firms that will restate in the future have interest rate spreads that are 27.64 basis points higher, on average, than comparable loans, after controlling for other predictors of loan spread. This supports the notion that banks have superior information access and processing skills relative to equity market participants because they can anticipate future restatements at the loan initiation date (Chen 2016). Moreover, we find some evidence that lenders are better able to anticipate future restatements when the loan initiation is preceded by one or more peer irregularities.…”
Section: Notessupporting
confidence: 84%
“…Prior research has found that investors, short sellers, and analysts are unable to anticipate restatement announcements, even when other firms in the same industry announce a restatement first (Drake et al 2015;Gleason et al 2008). Chen (2016) finds that banks, on the other hand, are able to identify risk factors correlated with misreporting well before such misconduct is publicly revealed. Our evidence suggests that peer restatements are one such risk factor that banks use to anticipate future restatements by the borrowing firm.…”
mentioning
confidence: 99%
“…This lag may affect inferences as banks are highly informed and may react before case outcomes are known, similar to insurers. Consistent with this, Chen () shows that banks respond to restatements before their public announcement.…”
Section: The Effect Of Securities Litigation On Dando Insurance and Intmentioning
confidence: 63%
“…15 They can expect more frequent and thorough bank inspection. If banks find indications of loss understatements or gain overstatements, it can hurt the borrower's trustworthiness, potentially leading to more scrutiny and less credit access (Chen 2016). To avoid these costs, borrowers have incentives to recognize losses in a timelier manner than gains, especially when they perceive an increased threat of bank inspection during tightening periods.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Meanwhile, borrowers can expect increases in the likelihood and intensity of bank inspections during tightening periods. When banks find signs of loss understatements or gain overstatements, this damages the borrower's trustworthiness, potentially resulting in more scrutiny and less credit access (Chen 2016). To avoid these costs, borrowers have incentives to recognize losses in a timelier manner than gains during tightening periods.…”
Section: Introductionmentioning
confidence: 99%